2013
DOI: 10.4314/jafs.v10i2.3
|View full text |Cite
|
Sign up to set email alerts
|

Cost and Return Analysis of Ginger Production in the Guinea Savannah of Nigeria

Abstract: The study focuses on the cost and return analysis of ginger production in the guinea savannah agro ecology of Nigeria. The study is aimed at highlighting the profitability of ginger production with a view to informing and influencing farmers and relevant stakeholders. The study was conducted at Kajuru, Kaduna state in the Guinea Savannah agro ecological zone of Nigeria, during the 2010 and 2011 planting seasons. The objectives of the study include: to estimate the cost and returns of ginger production, determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…But in the study by USAID (2011), GOK (2011) and Ewuziem & Onyenobi (2012) reported up to 46 %, 30.38% and 25% cost for seed respectively. The percentage of cost share observed on human labor and organic manure was 15.3% and 10.5% respectively in the study area.…”
Section: Cost Of Productionmentioning
confidence: 95%
“…But in the study by USAID (2011), GOK (2011) and Ewuziem & Onyenobi (2012) reported up to 46 %, 30.38% and 25% cost for seed respectively. The percentage of cost share observed on human labor and organic manure was 15.3% and 10.5% respectively in the study area.…”
Section: Cost Of Productionmentioning
confidence: 95%
“…The data series covered a period of five years (2008 to 2012). The national time series data, like those from central bank of Nigeria (CBN) or any relevant agency such as FAO could alternatively have been used, but it is a common fact to find differences in such data series from different sources (Manyoung and Nokoe 2003;Ojiako et al 2007;Ewuziem et al 2009). This explains the reliance on UN COMTRADE data.…”
Section: Methodsmentioning
confidence: 99%
“…The main competitors in ginger export are China, Nigeria and Thailand. In 2004, Nigeria's ginger export stood at 28,323mt valued at over $21.8m (Ewuziem et al 2009). This indicates that Nigeria occupies a very important position in world ginger cultivation and export.…”
Section: Estimates In Tablementioning
confidence: 99%
“…NdaNmadu revealed that labor, seed, fertilizer and capital inputs were significant in explaining the output [19]. contributed higher to the total variable cost of production [20].…”
Section: The Production Costs Of Gingermentioning
confidence: 99%